PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN BANYURIPAN, DESA BANYURIPAN KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , YULIANITA NURYANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final project describes about measurement and mapping to result a spatial data information from the Earthâs surface. Spatial data includes spot height and planimetric measurements obtained from the surface of the earth that will be presented in the form of situation map. Thatâs method horizontal measurement control is horizontal measurement control framework and vertical control framework, the measurement of planimetric detail and spot height, and also digital mapping. The final result is a situation that presents a map of spatial data on the earth's surface area designated areas at location 9 in the Banyuripan village, Bayat subdistrict, Klaten district in Central Java province in 1:500 scale projection system is UTM (Universal Transverse Mercator).